Análise de viabilidade da substituição dos perfis tubulares circulares por perfis em cantoneira simples na cobertura em estrutura espacial da rodoviária de Breu Branco/PA - SILVA, Helcio Mário Coelho da (2022)
The buildings executed in steel profiles have advanced greatly in recent decades in Brazil and among them the choice of structural system in space truss, however, still below the level of use of reinforced concrete. In large coverage areas, the spatial trussed steel are essential to win large spans, have low weight, ease of transportation, storage and assembly. The connection system (node) and the type of profile bars are factors that influence the cost savings, agility of construction and structural safety of a space truss. Thus, in this work, is prepared a study on the coverage, space truss, the road in the city of Breu Branco/PA. Aiming a comparative analysis in relation to cost and load capacity of the structural system used in the same, with circular tubular steel profile and connecting with typical node, and a new structural system with bars angle equal tabs and a new node for this profile For this, a computational analysis commercial software SAP® 2000 v14 was performed whereby the angle profile structure is suitable for scaled. For the cost analysis we used the composition table and Prices Budget (TCPO, 2010), developing spreadsheets composition of unit cost, considering the prices of services and current inputs in the city of Tucuruí/PA and the National System of prices and Supplies (SINAPI, 2014). It was found that the difference in steel consumption between the two types of profiles was small, with a percentage of 0,08%. Regarding the cost structure in bracket decreased value in the order of 30,93% over the circular tubular profile. As regards the practical implementation it was noted that the main difference is the type of connection where the node is typically realized by means of embossing the ends of the tubular bars, fixed with a single screw. However, the nodes of the angle profiles require a connection device node steel, made in welded steel sheets, using greater amounts of screws for fastening in relation to tubular profiles, and the difference in the total cost decreases but still the lattice in profile angle has lower cost than the lattice of tubular profile. Thus, it is observed that the use of the angle profile into spatial structures apresenta lower cost compared to tubular profiles. It was also observed that in addition to lower cost, the system with angle profiles, the structure has a higher efficiency due to more rigid connection of steel node compared to typical node.